Assange, WikiLeaks, and the liability of wiki providers for third party content. (1st January 2012) - Copp, Richard I.
The uploading of US diplomatic cables onto the WikiLeaks' wiki website has sparked widespread outrage. After more than a year, US authorities are reportedly still considering whether they can prosecute WikiLeaks and its founder Julian Assange. This paper investigates prosecution grounds under US and Australian Federal law. There is a possible case for both Assange and Wikileaks to answer in the USA, but the proof stakes are high. This may account for the delay in the US authorities commencing any proceedings to date. There appear to be no serious grounds for prosecution under Australian Federal law. The analysis has important implications for IT law. Wiki providers would appear not to be liable for publishing on their wikis defamatory or other material that does not clearly threaten national security. Nevertheless, a prudent wiki provider would monitor and remove very sensitive information.